The efficacy of Moina micrura enriched with probiotic Bacillus pocheonensis in enhancing survival and disease resistance of Red Hybrid Tilapia (Oreochromis spp.) larvae - Samat, Nur Amalina; Md Yusoff, Fatimah; Wan Rasdi, Wan Nadiah; Karim, Murni (Multidisciplinary Digital Publishing Institute, 2021)
The administration of probiotics via live feeds, such as Artemia and rotifers, has gained significant attention. Moreover, indiscriminate use of antibiotics in conventional aquaculture practices in order to prevent or control disease outbreaks has resulted in the occurrence of residues and antimicrobial resistance. Thus, the application of eco-friendly feed additives, such as probiotics, as a safer alternative has received increasing attention in recent years. However, only minimal information on the administration of probiotics via freshwater cladoceran Moina micrura is available despite being commonly used for larval and post-larval feeding of freshwater crustaceans and fish. Thus, this study aimed to evaluate the application of Bacillus pocheonensis strain S2 administered via M. micrura to red hybrid tilapia (Oreochromis spp.) larvae. Bacillus pocheonensis that has been previously isolated from Spirulina sp. was subjected to preliminary in vitro evaluation of antagonistic properties. The agar well-diffusion assay revealed that this probiont could inhibit the growth of Streptococcus agalactiae and Aeromonas hydrophila. The size of inhibition zones ranged from 8.8 ± 0.2 to 18.2 ± 0.4 mm. Moina micrura was later used as a biological model in preliminary in vivo bacterial challenge assays to evaluate the efficacy of B. pocheonensis in protecting the host from diseases. Moina micrura was pre-enriched with B. pocheonensis at 104 and 106 CFU mL−1 before S. agalactiae and A. hydrophila were introduced into the culture. The study revealed that B. pocheonensis at 104 CFU mL−1 was able to significantly enhance the survival of M. micrura after being challenged with both pathogens (63 ± 3%) in comparison to the control group. The relative percentage survival (RPS) of M. micrura was highest (p < 0.05) when treated with B. pocheonensis at both concentrations 104 and 106 CFU mL−1 (38.33) after being challenged against S. agalactiae. To assess the efficacy of B. pocheonensis in protecting red hybrid tilapia against streptococcosis, the larvae were fed with either unenriched (control) Moina or probiont-enriched Moina daily for 10 days. A significantly (p < 0.05) higher survival rate (77 ± 3%) was observed in larvae fed with probiont-enriched M. micrura compared to other treatments, and the RPS was recorded at 62.90. In addition, the S. agalactiae load was suppressed in larvae fed probiont-enriched M. micrura (6.84±0.39 CFU mL−1) in comparison to the control group (7.78±0.09 CFU mL−1), indicating that the probiont might have contributed to the improvement of tilapia health and survival. This study illustrated that M. micrura was suitable to be used as a vector for probiotics in freshwater fish larvae as an alternative to hazardous antibiotics for disease control.